الفحص الضريبي الإلكتروني كأحد آليات تطبيق التكنولوجيا الرقمية في إدارة الضرائب للحد من ظاهرة التهرب الضريبي - دراسة حالة مركز الضرائب بالأغواط(cdi) - سنوسي محمد الحبيب; بعاج الهاشمي (جامعة الوادي University of Eloued, 2024)
This study aimed to assess the impact of Electronic Tax Examination on the performance of the Performance of the tax center in Laghouat In its three dimensions (collection, transparency, fighting fraud and tax evasion).The study used structural equations as a methodological method to achieve its objectives, To achieve the study's objectives, a questionnaire was developed to collect data from a sample of 40 individuals from the tax center in Laghouat, Using SMART PLS software to analyze the data, The study showed that electronic tax examination positively affects the performance of the tax center, The study recommends the necessity of using digitization in the tax sector for its role in enhancing transparency, reducing effort, time and cost, and combating fraud and tax evasion.
Electronic tax examination as one of the mechanisms for applying digital technology in tax administration to Reduce Tax Evasion - Case study of the Laghouat Tax Center (CDI)
Keywords: فحص ضريبي الكتروني; مركز الضرائب; تحصيل; شفافية; محاربة الغش وتهرب الضريبي